Discipline processuali differenziate nei diritti amministrativi europei - SORACE, DOMENICO (Studi e saggi, 2009)
Discipline processuali differenziate nei diritti amministrativi europei. Anyone in Europe who considers that they have suffered an abuse of power on the part of a public body can apply to a judge for justice. But this role is not restricted to a single judge. Not only is there a plurality of judges corresponding to the plurality of States in which they exercise their functions, but also (in the majority of cases) within each State there is more than one type of judge appointed to impose respect of the law even on public bodies, just as the procedures and manner in which the judicial action may materialise are also different. The protection of the citizens is differentiated, and this can be explained by the varying requirements or the different motivations which cannot always justify the deriving complications. The book explores this phenomenon, considering some of the principal European State systems, as well as the system of the European Union itself.